Ekspresi Seni sebagai Media Moderasi Sosial Tionghoa dan Jawa pada Festival Imlek di Surakarta - Bondan Aji Manggala S.Sn., M.Sn.; Yuda Yedidyah Simamora (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2025)
The article about Artistic Expression as a Media for Chinese and Javanese Social Moderation at the Chinese New Year Festival in Surakarta aims to build awareness about a public event which was deliberately constructed to communicate harmonious values, familiarize Surakarta society with diverse races and religions and has a history of racial conflict between Chinese. and Java. Through forms of artistic expression and symbols at the Chinese New Year Festival in Surakarta, the values ​​of harmonization to live peacefully above diversity and dark history are voiced. This article was written using the perspective of structural semiotics theory to understand the moderation efforts made by the people of Sudiroprajan Village through the symbolization of art. This article examines the substance in the form of (1) the potential of festivals as a medium for cultural harmonization, (2) the forms and symbols of Chinese-Javanese harmonization in the Grebeg Sudiro Chinese New Year Festival in Surakarta, and (3) the mental modality of pluralism in the culture of Surakarta society. It is hoped that the results of the study in this article can inspire the growth of festivals or public events in Indonesia that promote harmonization between Indonesian society, which is full of diversity and prone to conflict.